Dave Sim : Conversations - Grace, Dominick, 1963-; Merritt, Kory (Book collections on Project MUSE., 2013)
In 1977, Dave Sim (b. 1956) began to self-publish Cerebus, one of the earliest and most significant independent comics, which ran for 300 issues and ended, as Sim had planned from early on, in 2004. Over the run of the comic, Sim used it as a springboard to explore not only the potential of the comics medium but also many of the core assumptions of Western society. Through it he analyzed politics, the dynamics of love, religion, and, most controversially, the influence of feminism--which Sim believes has had a negative impact on society. Moreover, Sim inserted himself squarely into t.